2022
DOI: 10.23960/jpp.v12.i3.2022010
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a Web-Based Instructional Tool in Higher Education in Technology Enabled Learning during the Covid-19 Pandemic

Abstract: YouTube as a Web-Based Instructional Tool in Higher Education in Technology Enabled Learning during the Covid-19 Pandemic. Objectives: YouTube became an alternative to face-to-face teaching during COVID-19, although its use among Bachelor of Science in Criminology students is sparse. This study evaluated YouTube as an instructional tool for Technology-Enabled Learning (TEL). Methods: This survey randomly sampled 281 BS Criminology students. Frequency, mean, percentage, and ANOVA were used in analyzing the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Using ICT and online learning applications, the teaching and learning process for teachers and learners become more independent, creative, flexible, and encourage students to increase their academic product (Nurjaman & Sabilah, 2022). Also, web-based instructional tool could improve students' sociability, grades, motivation to learn, and curriculum delivery when utilized technologyenabled learning (TLE) (Patalinghug & Patalinghug, 2022).…”
Section: Extent Of Implementation Of E-government Programs Along E-pa...mentioning
confidence: 99%
“…Using ICT and online learning applications, the teaching and learning process for teachers and learners become more independent, creative, flexible, and encourage students to increase their academic product (Nurjaman & Sabilah, 2022). Also, web-based instructional tool could improve students' sociability, grades, motivation to learn, and curriculum delivery when utilized technologyenabled learning (TLE) (Patalinghug & Patalinghug, 2022).…”
Section: Extent Of Implementation Of E-government Programs Along E-pa...mentioning
confidence: 99%
“…Libasin et al [12] concluded that students and lecturers worked together to ensure similar learning outcomes before the pandemic. The work of Patalinghug and Patalinghug [13] displayed that using YouTube as a web-based instructional tool improved students' sociability, grades, learning motivation, and curriculum delivery through utilizing technology-enabled learning. Revelo-Rosero et al [14] highlighted digital tools and resources available on the web to improve the teaching-learning process inside and outside the classroom.…”
Section: Introductionmentioning
confidence: 99%